Research Status and Prospect of Torsional Vibration Detection Methods for Rotating Machinery - GUO Yan-ling; QIU Feng; LI Zhi-peng (Journal of Harbin University of Science and Technology, 2021)
Torsional vibration of rotating machinery is one of the main factors affecting the reliability and service life of rotaing machinery. In recent years, the number of large units accidents caused by torsional vibration is increasing. Therefore, how to detect torsional vibration has become a major focus in the machinery increasing.The process of torsional vibration of detection method can be divided into two steps: the measurement of torsional vibration signals and the extraction and analysis of torsional vibration signal. The measurement methods of torsional vibration signal are divided into contact measurement method and non-contact measurement method. The extraction and analysis methods of torsional vibration signal are divided into Fourier transform method and signal decomposition method. We introduce each method of these methods, espound in detail the woking principle, reaserch significance, practical application, advantages and disadvantages of each methods, and finally forecast the development trend of these methods. It is expected to provide some reference and guidance for the future research on torsional vibration detection methods of rotating machinery